2012
DOI: 10.1080/10967494.2012.702590
|View full text |Cite
|
Sign up to set email alerts
|

Public Sector Organizations and Reputation Management: Five Problems

Abstract: This article discusses five problems that most public organizations will face when adopting a popular, yet largely unexplored management concept: reputation management. The inherently political nature of public organizations constrains their reputation management strategies. Furthermore, they have trouble connecting with their stakeholders on an emotional level, standing out as unique and differentiated organizations, communicating as coherent bodies, and maintaining excellent reputations. In this article, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
187
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(200 citation statements)
references
References 44 publications
(29 reference statements)
6
187
0
2
Order By: Relevance
“…How governments communicate will shape their legitimacy (Waeraas & Byrkjeflot, 2012), and legitimation has been seen as a particular mode of strategic communication in the public sector (Aggerholm & Thomsen, 2016); but legitimacy takes time to develop and extend (Grimmelikhuijsen & Meijer 2015). The elaboration of legitimacy typology was proposed to identify which is the angle citizens emphasize when assessing a central government's policy about refugees.…”
Section: Diplomacy Strategiesmentioning
confidence: 99%
“…How governments communicate will shape their legitimacy (Waeraas & Byrkjeflot, 2012), and legitimation has been seen as a particular mode of strategic communication in the public sector (Aggerholm & Thomsen, 2016); but legitimacy takes time to develop and extend (Grimmelikhuijsen & Meijer 2015). The elaboration of legitimacy typology was proposed to identify which is the angle citizens emphasize when assessing a central government's policy about refugees.…”
Section: Diplomacy Strategiesmentioning
confidence: 99%
“…As such, continuous study in this area is crucial to assist public organization to build a strong, favorable reputation [9]. In addition, reputation in public sector has been recognized as "valuable political assets" [6] used to generate public confidence to continuously supporting the government.…”
Section: Organizational Reputationmentioning
confidence: 99%
“…Previous research indicated that incidences involving regulatory bodies have resulted in declining public trust in government, a sign of unfavorable reputation [1]. More importantly, the decline in trust has implications for the public organizations in regard to the legitimacy of democratic governance [1,6]. As a politically appointed organization, public support and trust are utmost important to ensure the survival of the government in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Seen from the outside, there is little evidence of 'corporate communications' from the sector as such (cf. Waeraas & Byrkjeflot, 2012). Regarding nation branding, the presentations of Norway and Sweden as student destinations reproduce clichés.…”
Section: Discussionmentioning
confidence: 99%